2018
DOI: 10.1016/j.childyouth.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

At-risk youths' self-sufficiency: The role of social capital and help-seeking orientation

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…First, as parts of this study took place in a controlled research environment with multiple “live” contact moments between participants and researchers, nonspecific factors, such as motivation to quit smoking, expectations, therapeutic alliance, and mindset, may have played a large role in boosting smoking cessation in both intervention groups (Boot et al, 2013; Crum, Leibowitz, & Verghese, 2017; Crum & Phillips, 2015; Dweck, 2006; McCuller, Sussman, Wapner, Dent, & Weiss, 2006; Newman, Szkodny, Llera, & Przeworski, 2011). For example, it may be that our casual talks with participants during pretest and post-test measurements, whereby we tried to be independent and nonjudgmental listeners to their stories and to understand their personal reasons and needs to quit smoking, might have been effective by actively supporting this highly motivated group of participants to help them quit smoking (Lenkens et al, 2019; Schenk et al, 2018). These nonspecific effects can be very valuable (Crum et al, 2015; 2017), but they may have limited the effect of the game mechanics specifically, which may have been found with an otherwise wait-list control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, as parts of this study took place in a controlled research environment with multiple “live” contact moments between participants and researchers, nonspecific factors, such as motivation to quit smoking, expectations, therapeutic alliance, and mindset, may have played a large role in boosting smoking cessation in both intervention groups (Boot et al, 2013; Crum, Leibowitz, & Verghese, 2017; Crum & Phillips, 2015; Dweck, 2006; McCuller, Sussman, Wapner, Dent, & Weiss, 2006; Newman, Szkodny, Llera, & Przeworski, 2011). For example, it may be that our casual talks with participants during pretest and post-test measurements, whereby we tried to be independent and nonjudgmental listeners to their stories and to understand their personal reasons and needs to quit smoking, might have been effective by actively supporting this highly motivated group of participants to help them quit smoking (Lenkens et al, 2019; Schenk et al, 2018). These nonspecific effects can be very valuable (Crum et al, 2015; 2017), but they may have limited the effect of the game mechanics specifically, which may have been found with an otherwise wait-list control.…”
Section: Discussionmentioning
confidence: 99%
“…Several intervention programs integrate peer influence processes in one way or another, such as by including social skill training that is directed at helping youth say no to smoking peers, by nonsmoking youth's giving support and advice to smoking youths, or by suggesting to spend less time with their smoking peers (Golechha, 2016; Sussman & Sun, 2009). These programs remain highly problematic, however, for several reasons: (a) the content is still solely targeted at the individual instead of a broader peer group (Gabble et al, 2015), (b) imbalanced relationships between the support giver and support taker are not helpful (Lenkens et al, 2019), and (c) these programs instigate high resistance among young smokers (Harakeh & Van Nijnatten, 2016; Schenk et al, 2018; Wolburg, 2006).…”
Section: Barriers To Successful Smoking Cessation For Youthmentioning
confidence: 99%
See 2 more Smart Citations
“…This might also be true of those who experience a fear of stigma, including from the person who is providing the help [5]. In a study on at-risk adolescents and emerging adults, the interviewees indicated that they did not want any help, since they felt that others did not understand them, especially when they had not been through similar experiences [6, 7]. The formal care system is overrepresented by highly educated people [8], who in most cases do not have any personal experience of delinquent behavior or even with growing up in a criminogenic environment.…”
Section: Introductionmentioning
confidence: 99%